A STUDY OF TEACHING TECHNIQUES USED BY TEACHER IN TEACHING ENGLISH AT SMAN 1 JAYAPURA - Wirawan, Fajar; Winardi, Dio; Syaftinentias, Widi; Novita, Loly; Masran, Silviana (Ensiklopedia of Journal, 2024)
Teaching techniques are commonly used by English teacher in teaching English in Indonesia. The teacher uses teaching techniques to create equal learning opportunities to each student because each student has different needs and interests. SMAN 1 Jayapura is the first senior high schools in Jayapura, which was built on 1st August 1965. This school is also a favorite school. The students are from many ethnics in Indonesia such as Javanese, Sudanese, Melanesia, Toraja, Bugis, Moluccas, etc.In this descriptive qualitative research design, the researcher limited the problem to the teaching techniques used by English teacher in the tenth and eleventhth classes at SMAN 1 Jayapura. The subject of this study was one of the English teachers at SMAN 1 Jayapura. Therefore, the purposes of this research were to describe kinds of teaching technique used by the English teacher, and to explain the strengths and weaknesses the teaching technique used by the teacher in teaching English at SMAN 1 Jayapura. In collecting the data, the researcher used three kinds of instruments. They were observation checklist, interview guide and documentation.Based on the data, the researcher found that the teacher used complete the dialogue, transformation drill, antonyms/synonyms, scramble sentences, question and answer exercise, peer correction, fill the blank, reading aloud and small group tasks as the teaching techniques used in teaching English. Additionally, the researcher also found that there were several strengths of using teaching techniques in teaching English. Those strengths were the techniques could make students active in learning process and the students were focus to understand the material and also it can improve the Students’ skill in English. However, the researcher also found that the weakness of using teaching techniques in teaching English. The weakness was it was difficult for the teacher to get students’ attention. Key words: teaching techniques, teaching English SMAN 1